Studi of In Vivo Antidiabetic Activity of Namnam Leaves (Cynometra cauliflora) Extract in Sprague Dawley Rat - La Ode Sumarlin; Agik Suprayogi; Min Rahminiwati; Aryani Satyaningtijas; Hajar Hajar; Meyliana Wulandari (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2023)
Various treatments for Type 2 Diabetes Mellitus (T2DM) aim to alleviate hyperglycemia. Although natural products have been extensively utilized, their mechanism of action and efficacy as antidiabetic agents, particularly for T2DM, has not been extensively assessed in vivo. In this research, the leaves of the Namnam (Cynometra cauliflora) were extracted and tested for their activity as an antidiabetic agent. Sprague Dawley rats aged 3.5-4 months, weighing 200-250 g, were used as the experimental model, with a total of 30 individuals. The rats were induced with a high-fat diet and 30% sucrose until their blood glucose concentration reached ≥ 120 mg/dL. Subsequently, the rats were divided into four groups (groups 1, 2, 3, and 4). Over 21 days, changes in blood glucose, triacylglycerol, glycogen, and blood plasma insulin levels were assessed. The results demonstrated that the methanol extract of Namnam leaves (NLME) effectively reduced blood glucose levels by 23-34%, decreased plasma triglyceride levels by 13-30%, and increased liver glycogen levels by 68-96% compared to the control group (Diabetes). Among all the parameters assessed, NLME exhibited similar performance to metformin, a commonly prescribed diabetes medication (p<0.05). Furthermore, the study revealed that NLME exerted antidiabetic effects, particularly for T2DM, by promoting liver glycogen formation, enhancing insulin secretion control, facilitating glucose absorption by muscles, and restricting fat metabolism in the blood